Pathfinders in international psychology - Rich, Grant Jewell; Gielen, Uwe P. 1940- (International psychology (Charlotte, N.C.), 2015)
This book provides a global overview of pioneers in international psychology with contributions from distinguished authors from representative nations around the world. Chapters offer biographical profiles describing the personal histories and professional contributions of leading figures in psychology from across the globe that represent the diversity of psychology. This volume can serve as a core or supplemental text for a broad range of courses in Psychology, International Studies, and Education, with particular interest to those teaching international psychology, cross-cultural psychology, and history of psychology.